Assessment of Additional Risk Factors for Cardiovascular Disease and Awareness Among Adult Patients With Diabetes Mellitus: A Cross- Sectional Study From Northern Sri Lanka - Printhiny, M.; Rajeshkannan, N.; Suganthan, N. (Springer, 2022)
Cardiovascular diseases are the leading cause of death in people with type 2 diabetes. The assessment of additional risk factors for cardiovascular disease among diabetes patients and comparing current practices with the best practices can improve patient care. The aim of this study was to assess these additional risk factors and awareness of them among adult patients with diabetes mellitus.
Keywords: Physician inertia; Life style modifications; Northern Sri Lanka; Cardiovascular risk; Diabetes